The purpose of this research is Analysis And Design Of Data Warehouse At Warung Asri - Suryana, I Putu Agus Priska (International Journal of Engineering and Emerging Technology; Vol 5 No 2 (2020): July - December, 2020)
The purpose of this research is to help provide information in supporting the decision making process in the field of sales, purchasing and food inventory control at Warung Asri. With the support of a data warehouse, management can be assisted in making decisions faster and more precisely. The research methods carried out include ongoing system analysis, library research, designing data warehouses using the star schema method. The results of this study are the availability of a data warehouse that can produce fast and accurate information both about data sales and material stock, thus helping the owner in making decisions in determining the amount of stock and sales targets. The conclusion of this research is the application of this data warehouse can be a media to assist the management of Warung Asri Index Terms —Application, Information, Data warehouse, Star Schema